The CD153 vaccine is a senotherapeutic option for preventing the accumulation of senescent T cells in mice - Shota Yoshida (Nature Portfolio, 2020)
Senotherapy, the removal of aged T cells, is an effective approach to attenuate age-related diseases. Here the authors report a CD153 targeting vaccine that prevents the accumulation of senescent adipose tissue T cells in mice on high-fat diet, which is associated with improved glucose tolerance.